IS Governance Evaluation Using COBIT 5 Framework on the Central Statistics Agency of Banyumas District - Rudy Yaniar Sianida; Fiby Nur Afiana; Rizki Wahyudi (ICSE (Institute of Computer Sciences and Engineering), 2020)
ABSTRACT: The purpose of this study was to determine the level of capability at the Office of the Central Statistics Agency in Banyumas. Evaluate to find out how well the information system governance can operate at BPS that applies it to improve future performance. After evaluating, it is hoped that BPS will be able to produce higher-quality data because the government will use this data as a foundation for future development and as an evaluation of the results of development that have been carried out. The methodology used is a literature study, observation, interview, questionnaire and documentation by COBIT 5. The results achieved that the current BPS capability level is 3.25, which means it is at level 3 (established process). By being at level 3, BPS Office information system governance has been running well and has been able to achieve competitive and efficient business objectives of the agency in the use of information systems.ABSTRAK: Tujuan penelitian ini adalah untuk mengetahui tingkat kapabilitas pada Kantor Badan Pusat Statistik Kabupaten Banyumas. Melakukan evaluasi untuk mengetahui seberapa baik tata kelola sistem informasi dapat beroperasi pada BPS yang menerapkannya untuk memperbaiki prestasi di masa mendatang. Setelah dilakukan evaluasi, diharapkan nantinya BPS bisa menghasilkan data yang lebih berkualitas, sebab data ini nantinya akan digunakan oleh pemerintah sebagai landasan pembangunan di masa yang akan datang serta sebagai evaluasi hasil pembangunan yang telah dilaksanakan. Metodologi yang digunakan ialah studi pustaka, observasi, wawancara, kuesioner dan dokumentasi yang sesuai dengan COBIT 5. Hasil yang dicapai bahwa tingkat kapabilitas BPS saat ini yaitu 3,25 yang berarti berada pada level 3 (established process). Dengan berada pada level 3 maka tata kelola sistem informasi Kantor BPS sudah berjalan dengan baik dan sudah dapat mencapai tujuan bisnis instansi yang kompetitif dan efisien dalam penggunaan sistem informasi.